Assessment of Cdx2 polymorphism in Iranian women with polycystic ovary syndrome - Behdis Khansari; Hashem Nayeri; Maryam Ostadsharif (Middle East Fertility Society Journal, 2023)
Abstract Background Women’s fertility is affected by polycystic ovarian syndrome (PCOS) as an endocrine disorder with characteristic symptoms such as insulin resistance, polycystic ovaries, menstrual irregularities, and obesity. In polycystic ovarian syndrome, the vitamin D endocrine system is regulated by the vitamin D receptor (VDR) associated with type II diabetes, endocrine dysfunctions, and insulin resistance. Therefore, the current paper deals with the investigation of the connection between Cdx2 VDR gene polymorphism and the biochemical factors in obese PCOS women. Material and methods In the current case–control study, 40 obese women without PCOS and 38 obese women with PCOS were enrolled in May–September 2016. Insulin, IGF1, FBS, and HOMA-IR were examined for the participants along with the allelic and genotypic frequency of Cdx2 polymorphism G/A (rs11568820) from Isfahan Fertility and Infertility Center, Iran. The ASM-PCR (multiplex allele-specific PCR) technique was utilized in this regard. Results The age of PCOS women was less (P < 0.001) than the controls. In PCOS women, insulin, FBS, and HOMA-IR serum levels were higher than in the control women (all P values 0.05). For GG, AG, AA,A, and G Cdx2(A/G) genotypic/allelic frequencies were 84.2%, 15.8%, 0%, 7.9%, and 92.1% in cases and 87.5%, 12.5%, 0%, 6.3%, and 93.8% in controls, respectively. HOMA-IR (P = 0.047 and P = 0.033, respectively) and insulin than those with the AG genotype were in PCOS women with the GG Cdx2 genotype. The highest IGF-1 mean value (P = 0.020) was found for the AG genotype in PCOS. In our study, a significant relation was found only between PCOS and FBS, in terms of a logistic regression analysis of Cdx2 and parameters. Conclusion In the present study, it was indicated that the GG genotype in PCOS subjects was associated with the IGF-1, HOMA-IR, and insulin. Similarly, no association was found between obese PCOS patients and Cdx2 in the 1a promoter area of the VDR gene in our study.